Follow your gut: Relaying information from the site of left–right symmetry breaking in the mouse. Issue 6 (5th May 2014) - Saijoh, Yukio; Viotti, Manuel; Hadjantonakis, Anna‐Katerina
Summary: A central unresolved question in the molecular cascade that drives establishment of left–right (LR) asymmetry in vertebrates are the mechanisms deployed to relay information between the midline site of symmetry‐breaking and the tissues which will execute a program of asymmetric morphogenesis. The cells located between these two distant locations must provide the medium for signal relay. Of these, the gut endoderm is an attractive candidate tissue for signal transmission since it comprises the epithelium that lies between the node, where asymmetry originates, and the lateral plate, where asymmetry can first be detected. Here, focusing on the mouse as a model, we review our current understanding and entertain open questions concerning the relay of LR information from its origin. genesis 52:503–514, 2014. © 2014 Wiley Periodicals, Inc.